Engagement dan Pergaulan Pra-Nikah: Kajian Hukum Islam Atas Realitas Sosial Masyarakat Kontemporer - MUNTAZAR, NAZRIL; AKMAL, NAILATUL (JISH: Jurnal Ilmu Syariah dan Hukum, 2025)
Engagement (khitbah) is a social tradition practiced in many communities as a form of commitment between two individuals preparing for marriage. In modern contexts, engagement is often understood as an emotional and social bond that legitimizes closer interaction, including physical intimacy. However, in Islamic law, engagement does not carry legal consequences that equate the couple’s status with that of husband and wife. This study aims to examine patterns of interaction during the engagement period using a normative-theological approach. Analysis of primary Islamic legal sources such as the Qur’an, Hadith, and both classical and contemporary fiqh literature reveals that engagement is merely an initial promise toward marriage without granting rights or obligations equivalent to a valid marriage contract. Therefore, Islamic boundaries (hudūd syar‘iyyah) must be observed to prevent acts leading to fornication (zina) or the violation of personal dignity. Engagement should thus be seen as preparation for marriage, not as justification for free interaction, ensuring the sanctity of the marital institution.